Finite size effect on Sm3+ doped Mn0.5Zn0.5SmxFe2−xO4 (0≤x≤0.5) ferrite nanoparticles. Issue 7 (August 2015) - Yadav, Nisha; Kumar, Ashok; Rana, Pawan S; Rana, Dinesh S; Arora, Manju; Pant, R.P.
Abstract: Samarium doped Mn–Zn ferrite nanoparticles of composition Mn0.5 Zn0.5 Sm x Fe2− x O4 (0≤ x ≤0.5) have been synthesized by a chemical co-precipitation method for developing low Curie temperature stable ferrofluid. These samples were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Electron Paramagnetic Resonance (EPR) spectroscopy and search coil method analytical techniques for their structural, morphological and magnetic properties. X-ray diffraction patterns confirmed the formation of crystalline single spinel phase of as grown nanoparticles. Lattice parameter and lattice strain increases with the increase in Sm 3+ content. SEM images revealed the presence of ultrafine particles and their agglomerated structures in higher Sm 3+ ions concentration analogues. The stoichiometry of the final product agreed well with the initial substitution composition as evidenced by EDS data. Electron paramagnetic resonance (EPR) spectra proved the ferromagnetic nature of nanoparticles. The magnetic measurements by search coil method showed superparamagnetism for x =0, 0.1 the samples with saturation magnetization of 23.95 emu/g for Mn0.5 Zn0.5 Fe2 O4 sample which increases with rise in Sm 3+ ions content. The results are explained and correlated with the structural, morphological and magnetic properties for developing stable kerosene based ferrofluid by using these nanoparticles.